Congenital anomalies in children with postneonatally acquired cerebral palsy: an international data linkage study - Goldsmith, Shona (2022)
Comprehensive CA-CP Study Group: Ingeborg Barisic, Vlatka Bosnjak Mejaski, Emmanuelle Amar, Elodie Sellier, Sandra Julsen Hollung, Kari Klungsøyr, Paula Braz, Daniel Virella, Catherine Gibson, Karin Källén, Susan M Reid, Gareth Baynam, Dylan Gration, Michèle Hansen, Linda Watson